1996
DOI: 10.1149/1.1836686
|View full text |Cite
|
Sign up to set email alerts
|

A New Three‐Volt Spinel Li1 + x Mn1.5Ni0.5 O 4 for Secondary Lithium Batteries

Abstract: The spinel LiMn1.5Ni0.5O4 has been prepared at low temperature using a new sol‐gel process. X‐ray diffraction analysis reveals that the obtained material presents a cubic spinel structure with a unit cell parameter lower than that of stoichiometric LiMn2O4 . X‐ray photoelectron spectroscopy confirms the divalent state of doped nickel in the material. Furthermore, LiMn1.5Ni0.5O4 compound can intercalate a second lithium both chemically and electrochemically, leading to the formation of a new Li2Mn1.5Ni0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
218
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(232 citation statements)
references
References 0 publications
11
218
2
1
Order By: Relevance
“…It was recorded that these trends are not the same for Co 2+ and Co 3+ ions. The loss of stability which characterized the transition from Co(II) to Co(III) state and which was recorded by Amine et al [27,28], Duncan et al [29], Liu et al [30], Santhanam and Rambabu [31], and Aklalouch et al [32,33] has been satisfactorily explained in the Lattice Compatibility Theory (LCT) framework. The most probable explanation which can be provided through the Simha-Somcynsky theory lies in the expression of the Helmholtz free energy (see (3) and (7)).…”
Section: Lattice Compatibility Theory (Lct) and Simha-somcynsky Conjomentioning
confidence: 88%
“…It was recorded that these trends are not the same for Co 2+ and Co 3+ ions. The loss of stability which characterized the transition from Co(II) to Co(III) state and which was recorded by Amine et al [27,28], Duncan et al [29], Liu et al [30], Santhanam and Rambabu [31], and Aklalouch et al [32,33] has been satisfactorily explained in the Lattice Compatibility Theory (LCT) framework. The most probable explanation which can be provided through the Simha-Somcynsky theory lies in the expression of the Helmholtz free energy (see (3) and (7)).…”
Section: Lattice Compatibility Theory (Lct) and Simha-somcynsky Conjomentioning
confidence: 88%
“…Over the years,alarge varietyo fm ethods have been reported to synthesize LNMO.T he majority of these synthesis methods can be divided into those based on wet chemistry, which imply the formationo faprecursor in as olution (e.g., co-precipitation, [4,[15][16][17][18][19] sol-gelm ethod, [20][21][22][23] modifiedP echini method, [24][25][26] emulsion drying [27][28][29] ), and solid-state methods in which the reactants are heat-treated directly after mixing (e.g.,c ombinational annealingm ethod, [30,31] one-step solidstate method [32][33][34] ). Although the wet-chemistry methods are able to produce powders of high chemical homogeneity with an arrow size distribution at low annealingt emperatures, [3,15] the synthesis procedures are rather complex and costly because of the long processing times and expensive precursor materials required.…”
Section: Introductionmentioning
confidence: 99%
“…Among them doping with Ni could make the spinel structure LMO more stable, thus improving the circulation characteristics of the LIBs [16,17]. Amine et al [18] reported that the LiNi 0.5 Mn 1.5 O 4 (LNMO) used as the cathode material for LIBs presented high discharge capacity and good cyclic reversibility.…”
Section: Introductionmentioning
confidence: 99%